2019
DOI: 10.1002/ijc.32619
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 loss‐of‐function germline mutations are associated with esophageal squamous cell carcinoma risk in Chinese

Abstract: Esophageal squamous cell carcinoma (ESCC) occurs with highest frequency in China with over 90% mortality, highlighting the need for early detection and improved treatment strategies. We aimed to identify ESCC cancer predisposition gene(s). Our study included 4,517 individuals. The discovery phase using whole‐exome sequencing (WES) included 186 familial ESCC patients from high‐risk China. Targeted gene sequencing validation of 598 genes included 3,289 Henan and 1,228 moderate‐risk Hong Kong Chinese. A WES appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…The libraries for MHC-target sequencing were prepared and sequenced in the Illumina HiSeq platform according to manufacturer instructions 5 . Briefly, the pre-capture sequencing libraries were prepared with 100-200 ng genomic DNA after fragmentation to 300-400 bp by Covaris according to the KAPA HyperPrep Kits 58 and hybridized to the SeqCap EZ Choice Enrichment Kit (Roche). Each capture included 24 indexed libraries of blood DNAs.…”
Section: Methodsmentioning
confidence: 99%
“…The libraries for MHC-target sequencing were prepared and sequenced in the Illumina HiSeq platform according to manufacturer instructions 5 . Briefly, the pre-capture sequencing libraries were prepared with 100-200 ng genomic DNA after fragmentation to 300-400 bp by Covaris according to the KAPA HyperPrep Kits 58 and hybridized to the SeqCap EZ Choice Enrichment Kit (Roche). Each capture included 24 indexed libraries of blood DNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Esophageal cancer is the eighth most‐common cancer in the world and the sixth leading cause of cancer death . Esophageal squamous cell carcinoma (ESCC) is the major histological subtype, especially in certain countries, such as China .…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer is the eighth most-common cancer in the world and the sixth leading cause of cancer death. 1,2 Esophageal squamous cell carcinoma (ESCC) is the major histological subtype, especially in certain countries, such as China. 3 Despite the rapid development of medical technology and continuous improvements in early diagnostic techniques, advanced ESCC cases still account for~50% of cases and exhibit a 5-year survival rate of only 15-25%.…”
Section: Introductionmentioning
confidence: 99%
“…Our study initially confirmed the negative effect of CBFA2T2, PAQR4 or C21orf58 on HCC prognosis for the first time. Conversely, tetratricopeptide repeat (TPR) domain protein 39B (TTC39B, C9orf52) (T39), a high density lipoprotein (HDL) gene discovered in human genome wide association studies (GWAS) [44,45], is associated with atherosclerosis and steatohepatitis as well as inflammation [46]. HSPB3 is an unfavorable molecular biomarker in colorectal adenocarcinoma [47].…”
Section: Discussionmentioning
confidence: 99%